2005
DOI: 10.1074/jbc.m504821200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Scramblase 1 Binds to the Promoter Region of the Inositol 1,4,5-Triphosphate Receptor Type 1 Gene to Enhance Its Expression

Abstract: Phospholipid scramblase 1 (PLSCR1) is a multiply palmitoylated, endofacial membrane protein originally identified based on its capacity to promote accelerated transbilayer phospholipid movement in response to Ca 2؉ . Recent evidence suggests that this protein also participates in cell response to various growth factors and cytokines, influencing myeloid differentiation, tumor growth, and the antiviral activity of interferon. Whereas plasma membrane PLSCR1 was shown to be required for normal recruitment and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…34 IP3R1 is known to play a key role in IP3-mediated mobilization of intracellular calcium ion Ca21 stores from the endoplasmic reticulum in a variety of cells and tissues, and it is also essential for cell growth and differentiation. 44,45 IP3R1 expression in many cells is upregulated in response to ATRA, DMSO, and interleukin-1b.…”
Section: Ip3r1 (mentioning
confidence: 99%
See 1 more Smart Citation
“…34 IP3R1 is known to play a key role in IP3-mediated mobilization of intracellular calcium ion Ca21 stores from the endoplasmic reticulum in a variety of cells and tissues, and it is also essential for cell growth and differentiation. 44,45 IP3R1 expression in many cells is upregulated in response to ATRA, DMSO, and interleukin-1b.…”
Section: Ip3r1 (mentioning
confidence: 99%
“…PLSCR1 was previously reported to traffic into the nucleus and bind to a specific segment of the IP3R1 59-promoter and enhance transcription of this gene. 34 We therefore investigated the promotion of PLSCR1 binding to the IP3R1 gene promoter by wogonoside using EMSA. PLSCR1 binding to double-stranded oligonucleotides containing the IP3R1 promoter was upregulated after treatment with 150 mM wogonoside for 48 hours, while untreated cells showed little or no DNA binding in the promoter ( Figure 5C).…”
mentioning
confidence: 99%
“…Involvement of PLSCR1 in protein-protein interaction is becoming more evident. It has been proposed that PLSCR1 interacts with several cellular proteins involved in signaling pathways and acts as a transcription factor for the inositol 1,4,5-triphosphate receptor type 1 gene (23,53). In this study, we identified ECM1a as a novel protein interaction partner of PLSCR1 in human skin.…”
Section: Discussionmentioning
confidence: 73%
“…In summary, although PLSCR1 is a member of the PLSCR gene family of type II transmembrane endofacial plasma membrane proteins and is thought to contribute to the translayer movement of phosphatidylserine ("scrambling") and other membrane phospholipids, the function of PLSCR1 as a scramblase has been challenged (23,41,46,(51)(52)(53). From recent studies, it is becoming clear that the proteins labeled as "phospholipid scramblases" are not required for scramblase activation or activity (for an update on PLSCR, consult Ref.…”
Section: Discussionmentioning
confidence: 99%
“…101 GTAACCATG-TGGA 89 ), enhancing the transcription of this gene [104]. IP3R1 is known to play a key role in IP3-mediated mobilization of intracellular Ca 2+ stores from the ER in a variety of cells and tissues, and it is also essential for cell growth and differentiation [105,106].…”
Section: Wogonin and Wogonosidementioning
confidence: 99%